Pengaruh Intellectual Capital Terhadap Kinerja Keuangan Pada Perusahaan Real Estate dan Property Di Indonesia - Elan Kurniawan; Windy Yuliana (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2019)
This research aims to determine the influence of Intellectual Capital which consists of Human Capital Efficiency (HCE, Structural Capital Efficiency (SCE), and Capital Employed Efficiency (CEE) toward the financial performance of real estate and property companies listed in Indonesian Stock Exchange. The research populations are financial performance companies which are consistently listed in Indonesian Stock Exchange during the period 2010-2014. Which amounted 50 companies. The sampling technique used is purposive sampling technique. According to pre-defined criteria, the researcher obtains 20 sample companies. Type of data which is used is secondary data taken using the documnetation method through accessing the website www.idx.co.id. The data analysis technique which is used are simple regression and double regression analysis. The result of this research show that: (1) there is a positive and significant influence between Human Capital Efficiency (HCE) towards ROE, with a correlation coefficient 0,533, coefficient determination R2 is 0,284, (2) there is a positive and significant influence between Structural Capital Efficiency (SCE) towards ROE, with a correlation coefficient 0,471, coefficient determination R2 is 0,222, (3) there is a positive and significant influence between Capital Employed Efficiency (CEE) towards ROE, with a correlation coefficient 0,516, coefficient determination R2 is 0,266, (4) there is a positive and significant influence between Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), and Capital Employed Efficiency (CEE) simultaneously towards ROE, with doubled correlation coefficient is 0,653, coefficient determination Adjusted R2 is 0,409